Examination of Zinc Electrode Performance in Microbial Fuel Cells - Cek, Nurettin (Gazi Univ, 2017)
Microbial fuel cells are one of the systems of renewable and clean energy generating. One of the most important things in microbial fuel cells is bacterial growth. Composts rich in organic substances are commonly used in microbial fuel cells because they positively affect bacterial growth. In addition, in recent years, studies on the use of non-inert (metal etc.) electrodes have increased; while inert (usually carbon based etc.) electrodes are generally used in microbial fuel cells. The objective of this study is to evaluate zinc anode performance by using microbial fuel cells mixed with compost. Experiments were carried out in microbial fuel cell equipped with zinc anode electrode and graphite cathode electrode. According to experiments, zinc is a suitable anode electrode of that utilizes electrochemical and biochemical reactions and therefore the microbial fuel cell produces high power density (5.33 W/m(2)). Zinc, which has a good electrochemical and biochemical performance, undergoes corrosion. But, according to measurements and calculations made on the basis of literature the anode zinc electrode used in this study is located in the category of corrosion-resistant material. The zinc anode for microbial fuel cells is the promising electrode technology. The experiments; the microbial fuel cell in this study, electrolyte, electrode, biofuel source, biocatalyst, etc. shows that the parameters work in harmony.
Keywords: Microbial fuel cell; Bacteria; Organic materials; Zinc electrode; Renewable energy